KEMITRAAN NAZHIR DENGAN BANK SYARIAH DALAM MENGEMBANGKAN WAKAF UANG : STUDI PERBANDINGAN DI INDONESIA, BANGLADESH DAN YORDANIA - ABDULLAH UBAID (LPPM IAIN Parepare, 2015)
Islamic bank as a fnancial institution that manages the already famous and no doubt its existence. Another case when the Islamic bank is associated with the endowment money. Not many people know, and still sparked many questions. This article intends to describe the institutional instrument cash waqf in Islamic banks. In some countries, in developing the waqf money, Nazhir not only work alone. But, he involves the Islamic bank as a strategic partner in the management of waqf money. This is the difference with cash waqf endowments of land, because the money including the type of property that is moving and more easily lost. In fact, the main task is to manage the property Nazhir endowments to be productive, not spend. Therefore, in order waqf money is not slim down, then took Nazhir Islamic bank as a partner in its management. This step has been done in several countries: among them are Indonesia, Bangladesh and Jordan. Difference model of partnership between Nazhir waqf money with Islamic banks in the three countries is what is described in this article